2008 3rd IEEE Symposium on New Frontiers in Dynamic Spectrum Access Networks 2008
DOI: 10.1109/dyspan.2008.34
|View full text |Cite
|
Sign up to set email alerts
|

Incentives and Resource Sharing in Spectrum Commons

Abstract: Abstract-It has been suggested that light regulation in the form of etiquette protocols, device design and bargaining amongst users will suffice to mitigate a tragedy of the commons in unlicensed spectrum. In this paper we propose a game theoretic model to examine this claim. In this game, each user decides whether or not to set up an access point, which operates on a particular (single) band. The effect of regulation is modeled in reduced form through transfers. A user who sets up an access point, provides pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…As the users have equal rights to access the spectrum, it is difficult to avoid the interference between the users transmitting on the same channels, which leads to the packet collisions and high rate of packet retransmission, thus decreasing the overall network throughput. Different centralised and distributed spectrum sharing strategies designed to minimise the interference problem were investigated in [10], [11] and [12].…”
Section: B Dynamic Spectrum Access Modelsmentioning
confidence: 99%
“…As the users have equal rights to access the spectrum, it is difficult to avoid the interference between the users transmitting on the same channels, which leads to the packet collisions and high rate of packet retransmission, thus decreasing the overall network throughput. Different centralised and distributed spectrum sharing strategies designed to minimise the interference problem were investigated in [10], [11] and [12].…”
Section: B Dynamic Spectrum Access Modelsmentioning
confidence: 99%
“…[28] studies a revenue maximization problem in a Stackelberg game, where spectrum owner, primary users and secondary users are the players for opportunistic spectrum access. Besides, authors in [27] build a game theoretic model to investigate whether light regulation in the form of etiquette protocols, device design and bargaining amongst users can avoid the tragedy of common in unlicensed spectrum. In terms of nonlinear dynamics in the economics, authors in [15] have shown that the bounded rationality can cause chaotic behaviors in a Cournot duopoly.…”
Section: Related Workmentioning
confidence: 99%